Office procedures - Moon, Harry R. (Bronx, New York : MPC Educational Publishers, 1984)
The publication of the third edition of OFFICE PROCEDURES marks the continuation of a new concept in the training of students preparing for office and secretarial careers. The overall objective of this textbook is to provide students preparing for office and secretarial careers with the knowledges and skills needed to meet entry-level requirements in today's business world.
Part 1. Basic Office Procedures -- Part 2. The Secretarial Specialist.
Includes bibliographical references.
Keywords: OFFICE PRACTICE